Catalog of the Ulidiidae (Diptera: Tephritoidea) of Chile - Mello, Ramon Luciano; González, Christian R.; Elgueta, Mario; Camargo, Alexssandro; Barahona-Segovia, Rodrigo M. (Zootaxa, 2024)
A catalog of Ulidiidae, picture-winged flies, from Chile is provided. Included are all valid names and synonyms for the 16 species and nine genera known from Chile, including information about name, author, year of publication, page number, type species, type locality, and references. Euxesta Loew is the more species richness genus in Chile, with five species, followed by Ceroxys Macquart, with two species. Besides, the lectotype and three paralectotypes of Ortalis fasciata Wiedemann, 1830, now in Pterotaenia, are here designated. A discussion about the distribution and biology of the picture-winged flies’ species in Chile is presented.